Cord Serum Lipid Profile of Infants of Diabetic Mothers - Jasim Almusawi (Mashhad University of Medical Sciences, 2015)
Background: Infants of diabetic mothers (IDM) is a critical issue in pediatrics, which is regarded as a major risk factor for birth trauma, respiratory distress syndrome (RDS), birth asphyxia, transient tachypnea of the newborn (TTN) and jaundice. IDM is also a risk factor for microvascular (e.g., ocular and renal complications) and macrovascular complications (e.g., cerebrovascular accident, atherosclerosis and cardiovascular complications). Lipids are a heterogeneous group of hydrophobic organic molecules which can be extracted from tissues using non-polar solvents. Lipids, due to their hydrophobic property, are mainly found in membranes enclosing various cell organelles. Diabetes mellitus management with insulin (nowadays also with oral hypoglycemic medications) has improved the outcomes of gestational diabetes mellitus (GDM) (most infants born to diabetic mother are large for gestational age). The neonatal mortality rate in IDM is over five times higher than that of infants of non-diabetic mothers. In this study, therefore, we aimed to assess the effect of maternal diabetes on cord serum lipid profile. Methods: This prospective (case-control) study was carried out on 60 infants born in Al-Zahra teaching hospital during February 2014-October 2014. The study group consisted of 30 randomly chosen IDM, and the control group comprised 30 infants who were born to healthy mothers. Results: The results of this study demonstrated that there are significant differences between IDM and infants of healthy mothers regarding lipid profile and birth weight. Conclusion: This study confirms that cord serum lipid profile (serum cholesterol, serum triglycerides and low-density lipoprotein) is higher at birth in IDM. Moreover, this study shows a significant association between lipid profile and body weight.